Auditory-Verbal Therapy. Teach to listen to learn to speak - Maggio De Maggi, Mariana (Auditio, 2021)
Auditory-Verbal Therapy is a therapeutic approach to the education of deaf children where the development of auditory skills through hearing are emphasized for the acquisition of language. To do this, hearing-impaired children must be detected diagnosed and equipped with optimal amplification as early as possible. Parents are taught to create an environment where their child learns to listen, process verbal language, and speak. In this article, a brief historical review of the development of this methodology is made and its fundamental principles related to audiological evaluation, prosthetic fitting, functional use of hearing and family-centered intervention are extensively described.